Effect of Core Stability Training on Throwing Accuracy and Bat Swing Mechanics in Competitive Pakistani Baseball Players: A Randomized Controlled Trial (Contemporary Journal of Social Science Review, 2025)
Background: Core stability is fundamental to kinetic chain efficiency in overhead throwing and rotational hitting sports. Despite its well-established role in athletic performance, no study has examined core stability training (CST) effects on baseball-specific skill outcomes in Pakistani players.Objective: To determine the effect of an eight-week structured CST program on throwing accuracy and bat swing mechanics in competitive Pakistani male baseball players.Methods: A randomized controlled trial was conducted with 80 competitive male baseball players (mean age: 21.4 ± 2.7 years) affiliated with the Pakistan Baseball Federation. Participants were randomly allocated to a Core Stability Training Group (CSTG; n = 40) or a Control Group (CG; n = 40). The CSTG completed a progressive, four-phase CST program (3 sessions/week, 8 weeks), while the CG continued standard training. Primary outcomes were throwing accuracy (mean radial error) and bat swing velocity, assessed using three-dimensional motion capture (Vicon Nexus, 200 Hz), radar measurement, and a target accuracy grid protocol. Core stability was assessed via the McGill Core Endurance Battery and Pressure Biofeedback Unit (PBU) test. Between-group differences were analyzed using ANCOVA (controlling for baseline), with Cohen's d effect sizes reported.Results: The CSTG demonstrated significantly greater improvements than the CG in mean radial error (−31.2%; d = 1.54; p < 0.001), bat swing velocity (+10.2%; d = 1.27; p < 0.001), and hip-to-shoulder separation angle (+14.6°; d = 2.40; p < 0.001). McGill Composite Score and PBU scores were the strongest independent predictors of post-intervention throwing accuracy (β = −0.54) and bat swing velocity (β = 0.49), respectively. All between-group differences were statistically significant (p < 0.001).Conclusion: An eight-week structured CST program produces large-magnitude improvements in throwing accuracy and bat swing mechanics in competitive Pakistani baseball players. These findings support the integration of progressive core stability work into evidence-based training programs within the Pakistani baseball ecosystem.